PERANAN GURU BIMBINGAN KONSELING PADA ANAK USIA DINI - Fauziah Nasution; Insyafiatul Ummi; Jasmine Dwi Aulia; Luthfia Rizka; Rahma Adlya (Al-Abyadh, 2023)
The objective of this research is to elucidate the influence of counseling and guidance on the development of character in young children. The study employs design research as its methodology. By utilizing design research, it was concluded that not only parents but also counseling teachers play a crucial role in shaping a child's character. Offering appropriate guidance and counseling can positively impact the formation of children's character. As children progress through their developmental stages, they may face various obstacles that hinder their growth. Inconsistencies in a child's development can arise from issues related to the child themselves. Both the family environment and the play environment contribute to these challenges faced by children. Such issues can lead to behaviors like arrogance, excessive emotions, anxiety, and so on. School counselors should employ counseling techniques suitable for the child's age in order to enhance their character. Early childhood problems necessitate counseling interventions. Consequently, the implementation of guidance and counseling during early childhood has a profound influence on the future development of character.